Separation, Purification, Structure Analysis, In Vitro Antioxidant Activity and circRNA-miRNA-mRNA Regulatory Network on PRV-Infected RAW264.7 Cells of a Polysaccharide Derived from Arthrospira platensis - Mi-Xia Cao; Xiao-Dong Xie; Xin-Rui Wang; Wen-Yue Hu; Yi Zhao; Qi Chen; Lu Ji; Ying-Yi Wei; Mei-Ling Yu; Ting-Jun Hu (MDPI AG, 2021)
To investigate the structure of Arthrospira platensis polysaccharide (PAP) (intracellular polysaccharide) and the antioxidant activity of the first component of PAP (PAP-1) on pseudorabies virus (PRV) -infected RAW264.7 cells. The PAP was separated and purified by the Cellulose DE-52 chromatography column and Sephacryl S-200 high-resolution gel column to obtain PAP-1. The antioxidant activity and regulation of PAP-1 on PRV-infected RAW264.7 cells of circRNA-miRNA-mRNA network were investigated by chemical kit, Q-PCR, and ce-RNA seq. The results indicated that the molecular weight (Mw) of PAP-1, which was mainly composed of glucose and eight other monosaccharides, was 1.48 × 106 Da. The main glycosidic bond structure of PAP-1 was →4)-α-D-Glcp-(1→. PAP-1 may be increased the antioxidant capacity by regulating the circRNA-miRNA-mRNA network in PRV-infected RAW264.7 cells. This study provided a scientific foundation for further exploring the antioxidant activity of PAP-1 based on its structure.